2008
DOI: 10.1016/j.resp.2008.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen in obstructive sleep apnea: Role of loop gain

Abstract: We compared the effect of oxygen on the apnea-hypopnea index (AHI) in six obstructive sleep apnea patients with a relatively high loop gain (LG) and six with a low LG. LG is a measure of ventilatory control stability. In the high LG group (unstable ventilatory control system), oxygen reduced the LG from 0.69+/-0.18 to 0.34+/-0.04 (p<0.001) and lowered the AHI by 53+/-33% (p=0.04 compared to the percent reduction in the low LG group). In the low LG group (stable ventilatory control system), oxygen had no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(165 citation statements)
references
References 32 publications
5
152
0
8
Order By: Relevance
“…In a recent meta-analysis of the effects of oxygen therapy in over 300 OSA patients, Mehta et al 30 demonstrated that oxygen reduced the AHI by 20% (18% to 28% interquartile range). Similarly, our previous work 22 demonstrated that oxygen therapy reduced the AHI by 33%, with 2 of 12 patients (17%) being considered responders using the definition used in the current study. Furthermore, we have shown 23 that the hypnotic eszopiclone reduced the AHI by a similar magnitude as oxygen (22%), with 2 of 17 patients (12%) considered responders.…”
Section: Combining Oxygen and A Hypnotic Has An Additive Effect In Resupporting
confidence: 79%
See 3 more Smart Citations
“…In a recent meta-analysis of the effects of oxygen therapy in over 300 OSA patients, Mehta et al 30 demonstrated that oxygen reduced the AHI by 20% (18% to 28% interquartile range). Similarly, our previous work 22 demonstrated that oxygen therapy reduced the AHI by 33%, with 2 of 12 patients (17%) being considered responders using the definition used in the current study. Furthermore, we have shown 23 that the hypnotic eszopiclone reduced the AHI by a similar magnitude as oxygen (22%), with 2 of 17 patients (12%) considered responders.…”
Section: Combining Oxygen and A Hypnotic Has An Additive Effect In Resupporting
confidence: 79%
“…22,26 Furthermore, we observed a significant correlation between the reduction in loop gain and the reduction in OSA severity, suggesting that those who had the greatest decrease in loop gain benefit substantially from combination therapy. This finding supports a causal role for loop gain in OSA pathogenesis and suggests that maximally lowering loop gain will likely resolve OSA in patients with relatively "good" passive anatomy/collapsibility and a small physiological "gap."…”
Section: Altering Loop Gainmentioning
confidence: 65%
See 2 more Smart Citations
“…Their concept of OSA phenotyping raises the opportunity for alternatives to continuous positive airway pressure (CPAP) in reducing AHI in selected patients, such as oxygen supply and/or acetazolamide lowering the loop gain and hypnotics elevating the arousal threshold. [20][21][22] We did not directly compare our approach to measures and interventions available only in a physiologic laboratory nor have we estimated these specific phenotypes, but instead demonstrate how signals usually available in clinical polysomnography can be informative. Although the treatment effects were not examined in our current study, one might predict that those who showed greater change in ventilation and in PaCO 2 back and forth between sleep and wakefulness, and showed NREM-predominant apneic events might be able to be treated effectively with oxygen supplement therapy and/or hypnotic agents.…”
Section: Discussionmentioning
confidence: 99%